Karakteristik Fisikokimia dan Organoleptik Cokelat Batang dengan Variasi Konsentrasi Tepung Kacang Merah (Phaseolus vulgaris L.) - Risky Rahmaniar; Elok Pawening Maharani; Subekti Hartiningsih (Universitas Bumigora, 2026)
Cocoa is a high-value commodity that can be processed into chocolate. One potential innovation is the addition of red beans as a source of plant-based protein in chocolate bars. The objective of this study was to analyze the effect of red bean flour on the physicochemical and sensory characteristics of chocolate bars. The research method used was a Completely Randomized Design (CRD) with red bean flour concentrations of 0%, 5%, 10%, and 15% (w/w). Based on the results, the use of red bean flour had a significant effect on reducing the hardness of the chocolate product from 4389.5 gf (0%) to 2672.3 gf (15%). However, the addition of red bean flour had no significant effect on moisture content and met SNI standards (<2%). The panelists’ acceptance scores ranged from 3.28 to 3.74, with the optimal treatment achieved at a 5% red bean flour content. In conclusion, the addition of 5% red bean flour produced chocolate bars with the best physicochemical and organoleptic characteristics; thus, it is expected to contribute as an innovative, value-added product alternative that supports the diversification and development of the chocolate industry.